A Study of Trends and Magnitude of Farmer Suicides in India: Understanding the Crisis and its Impact (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Farmer suicides have become so rampant in India that the phrase sounds more like a growing epidemic. More than three lakh farmers, including both cultivators and agricultural labourers, have committed suicide in India between 1995 and 2014. This is roughly equivalent to a shocking figure of one farmer suicide every 30 minutes. The severity of problem of suicides increased among farmers, relative to other occupational groups, after 2001. The rate of farmer suicides which ranged between 1.4 to 1.8 per lakh of population till 2005 has increased to 14.5 per lakh in 2011. The marginal and small farmers holding less than 2 hectare of land constitute 72.4% of total farmer suicides in India. Hence, it is an alarming issue to be looked into with great concern and introspected with extreme delineation. There is a wide array of factors that has led to the increasing spate of farmer suicides in India. The main focus of this study is to find out the ground realities of farmer suicides in India, reasons behind farmer suicides as well as the trends and magnitude of farmer suicides between 1995 and 2014.